STUDI KOMPARATIF TINGKAT PRODUKTIVITAS PRODI AKUNTANSI DI INDONESIA PADA KEGIATAN PENELITIAN, PENGABDIAN KEPADA MASYARAKAT DAN PUBLIKASI BERBASIS DATA SINTA - Dini, Maya; Ikraam, Ikraam (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2024)
In the industrial era 4.0, Accounting Study Programs in Indonesia face challenges in the form of increasingly fierce competition. The key word for winning the competition is competitiveness, both at the local, regional, national and international levels. Competitiveness can be measured from the performance of lecturers in carrying out research activities, community service (hereinafter referred to as service) and publications. In this regard, there is a need for research results that measure competitiveness at the study program level, one of which is measured through the level of lecturer productivity. Not only calculating productivity, this research also conducted a comparative analysis of accounting study programs at PTN with PTS and accounting study programs in Java and outside Java. Therefore, it is very important to carry out this research so that it can become a reference document in revealing the productivity of accounting study program lecturers and seeing the comparison between PTNs and PTSs as well as between Java and outside Java. This research has three objectives: First, to determine the level of productivity of the accounting study program in producing research, service and publications. Second, to analyze whether there are differences in productivity levels between accounting study programs at PTN and PTS. Third, to analyze whether there are differences in productivity levels between accounting study programs in Java and outside Java. The research method uses a quantitative approach which processes secondary data using independent sample test analysis using SPSS 21 software. Keywords: Comparative; Productivity; Research; Community Service, Publication